Baseline vascular endothelial growth factor concentration as a potential predictive marker of benefit from vandetanib in non-small cell lung cancer. - Hanrahan, E; Ryan, A; Mann, H; Kennedy, S; Langmuir, P; Natale, R; Herbst, R; Johnson, B; Heymach, J (2009)
PURPOSE: Vandetanib [vascular endothelial growth factor (VEGF) receptor/epidermal growth factor receptor/RET inhibitor] has shown improvements in progression-free survival (PFS) in advanced non-small cell lung cancer in three randomized phase II studies: vandetanib versus gefitinib (study 3), docetaxel +/- vandetanib (study 6), and carboplatin-paclitaxel and/or vandetanib (study 7). In study 7, vandetanib monotherapy was inferior to carboplatin-paclitaxel. We performed an exploratory retrospective analysis of the relationship between baseline circulating VEGF concentrations and PFS. EXPERIMENTAL DESIGN: Mean baseline VEGF levels were determined by ELISA from two baseline samples of plasma (163 of 168 patients, study 3; 65 of 127, study 6) or serum (144 of 181, study 7). High baseline VEGF values were above the immunoassay reference range for healthy subjects; low baseline VEGF values were within the range. RESULTS: Patients with low baseline VEGF had a lower risk of disease progression with vandetanib versus gefitinib [hazard ratio (HR), 0.55; 95% confidence interval (95% CI), 0.35-0.86; P = 0.01] or vandetanib 100 mg/d + docetaxel versus docetaxel (HR, 0.25; 95% CI, 0.09-0.68; P = 0.01). High VEGF patients had a similar risk of disease progression with vandetanib monotherapy versus gefitinib (HR, 1.03; 95% CI, 0.60-1.75; P = 0.92) or vandetanib 100 mg/d + docetaxel versus docetaxel (HR, 0.95; 95% CI, 0.25-3.61; P = 0.94). In study 7, low VEGF patients had a similar risk of disease progression with vandetanib monotherapy 300 mg/d versus carboplatin-paclitaxel (HR, 0.80; 95% CI, 0.41-1.56; P = 0.51); high VEGF patients progressed more quickly (HR, 1.60; 95% CI, 0.81-3.15; P = 0.17). CONCLUSIONS: These analyses suggest that low baseline circulating VEGF may be predictive of PFS advantage in patients with advanced non-small cell lung cancer receiving vandetanib versus gefitinib or vandetanib + docetaxel versus docetaxel. Moreover, patients with low VEGF levels may have a similar outcome with either vandetanib monotherapy or carboplatin-paclitaxel.